Механізми зниження інноваційно-інвестиційних ризиків у конфліктній економіці: досвід України - Ткаченко, А.М.; Межерицький, Д.А. (Економічний вісник Донбасу, 2026)
У статті досліджено механізми зниження інноваційно-інвестиційних ризиків, що застосовуються в Україні в умовах повномасштабної війни. Проаналізовано систему багаторівневих гарантійних інструментів, включаючи механізми Багатостороннього агентства з гарантування інвестицій (MIGA), Фінансової корпорації розвитку США (DFC) та Рамкової програми інвестування України (Ukraine Investment Framework). Виявлено мультиплікативний ефект донорського фінансування та оцінено ефективність залучення приватного капіталу. В роботі дана оцінка впливу інноваційно- інвестиційних ризиків на зайнятість, а також обґрунтовано механізм переходу від екстреної підтримки до довгострокового розвитку після завершення конфлікту. The article examines the unique system of investment risk mitigation mechanisms created in Ukraine during the full-scale war. A multilevel architecture of guarantee instruments is analyzed, including mechanisms of the Multilateral Investment Guarantee Agency, the U.S. Development Finance Corporation, and the Ukraine Investment Framework. A multiplicative effect of 4.4:1 for MIGA donor financing has been identified. Specific investment cases totaling over USD 15 billion have been studied. A comparative analysis with post-conflict economies of Iraq, Afghanistan, the Western Balkans, and Colombia has been conducted. The research analyzes the transformation of the investment landscape, including the collapse of foreign direct investment to USD 0.22 billion in 2022 and recovery to USD 4.6 billion in 2023. The structure of financing for landmark transactions is examined, including the OKKO Wind project (EUR 225 million), NJJ Holding telecommunications acquisition (USD 1.5 billion), and multilevel financing for Astarta agribusiness (USD 78 million). The study reveals critical sectoral selectivity, with over 95% of investments concentrated in five sectors, while capital-intensive industries remain underinvested. War risk insurance pricing is analyzed, demonstrating that Ukrainian rates of approximately 1% with subsidized mechanisms are moderate compared to other conflict zones. Recommendations are formulated for expanding coverage to small enterprises, launching a state system for war risk insurance, and creating specialized mechanisms for renewable energy.